Predischarge Screening for Severe Neonatal Hyperbilirubinemia Identifies Infants Who Need Phototherapy - Bhutani, Vinod K.; Stark, Ann R.; Lazzeroni, Laura C.; Poland, Ronald; Gourley, Glenn R.; Kazmierczak, Steve; Meloy, Linda; Burgos, Anthony E.; Hall, Judith Y.; Stevenson, David K. (The Journal of pediatrics, 2013)
To test whether the combined use of total plasma/serum bilirubin (TSB) levels and clinical risk factors more accurately identifies infants who receive phototherapy than does the use of either method alone. We recruited healthy infants of ≥35 weeks' gestation at 6 centers that practiced universal predischarge TSB screening. Transcutaneous bilirubin (TcB) was measured at 24 hours, with TSB at 24-60 hours and at 3- to 5- and 7- to 14-day follow-up visits. Clinical risk factors were identified systematically. Of 1157 infants, 1060 (92%) completed follow-up, and 982 (85%) had complete datasets for analysis. Infant characteristics included 25% were nonwhite and 55% were Hispanic/Latino; >90% were breastfed. During the first week, jaundice was documented in 84% of subjects. Predischarge TSB identified the 41 (4.2%) and 34 (3.5%) infants who received phototherapy before and after discharge, respectively. Prediction of postdischarge phototherapy was similar for combined clinical risk factors (earlier gestational age [GA], bruising, positive direct antiglobulin test, Asian race, exclusive breastfeeding, blood type incompatibility, jaundice extent) and age-adjusted TSB (area under the curve [AUC] = .86 vs .87), but combined screening was better (AUC = .95). TcB/TSB combined with GA alone was equally predictive (AUC = .95; 95% CI .93-.97). Jaundice is present in 4 of 5 (84%) healthy newborns. Predischarge TcB/TSB (adjusted for postnatal age) combined with specific clinical factors (especially GA) best predicts subsequent phototherapy use. Universal implementation of this strategy in the US should improve outcomes of healthy newborns discharged early.